The development and validation of the beliefs about Baby Crying at Night (BBCN) scale - Gustin, Marie-Paule; Lecuelle, Florian; Anders, Royce; Leslie, Wendy; Franco, Patricia; Putois, Benjamin (Sleep medicine, 2024)
What are young children trying to express when they cry at night? According to Sadeh, parental beliefs about why their child is crying may play a role in the development and persistence of their child's insomnia. The aim of this study was to create a scale that specifically assesses these parental interpretations in different dimensions. Children aged between 6 months and 3 years with either good sleep habits or behavioural insomnia were recruited. An initial, 20-item scale for the beliefs of why one's baby is crying at night was developed, with all items on a 7-point Likert span. The results of this scale from a large sample were then submitted to Exploratory (EFA) and confirmatory (CFA) factor analyses to converge on a final version and evaluate its psychometric properties and validity. Among the 1009 subjects included in the analyses (46.2 % female, mean age: 1.63 ± 0.73, good sleepers n = 425 and bad sleepers n = 584). After the factor analysis was performed, a 14-item scale with 4 subscales quantifying each interpretation type resulted: namely, “Need for attachment” (5 items), “Need to cry before falling asleep” (3 items), “Leaving a child to cry during the night is traumatizing for the child” (4 items) and “Is in pain” (2 items). The CFA further confirmed an appropriate fit. The most divergent subscale between groups was the “Need for attachment” subscale. This study proposes the first scale known to focus exclusively on parent interpretations of their child's night-time crying, without taking into account their nursing behaviours. It provides a clinical tool for more effectively discussing with parents, in order to address potential dysfunctional beliefs in the context of early childhood insomnia complaints, as well as a research tool for considering cognitive dimensions in the aetiology and treatment of behavioural insomnia. •The BBCN scale consists of 14 items divided into four interpretative dimensions.•First dimension: the baby is crying because it has a Need for attachment.•Second dimension: a natural Need to cry before falling asleep.•Third dimension: Leaving a child to cry during the night is traumatizing for the child.•Fourth dimension: crying to express or signal being in Pain.